2018
DOI: 10.3389/fpls.2018.00305
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solid Biological Waste Compost on the Metabolite Profile of Brassica rapa ssp. chinensis

Abstract: Large quantities of biological waste are generated at various steps within the food production chain and a great utilization potential for this solid biological waste exists apart from the current main usage for the feedstuff sector. It remains unclear how the usage of biological waste as compost modulates plant metabolites. We investigated the effect of biological waste of the processing of coffee, aronia, and hop added to soil on the plant metabolite profile by means of liquid chromatography in pak choi spro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 77 publications
1
3
0
Order By: Relevance
“…The observed inverse relationship between carotenoids and flavonoids is in accordance with literature, where several studies revealed antagonistic occurrence of carotenoid and flavonoid content within different treatments ( Ngwene et al., 2017 , Ben Cao et al., 2015 ; Abdallah et al., 2016 ; Neugart et al., 2018 ). For instance, Becker et al.…”
Section: Discussionsupporting
confidence: 92%
“…The observed inverse relationship between carotenoids and flavonoids is in accordance with literature, where several studies revealed antagonistic occurrence of carotenoid and flavonoid content within different treatments ( Ngwene et al., 2017 , Ben Cao et al., 2015 ; Abdallah et al., 2016 ; Neugart et al., 2018 ). For instance, Becker et al.…”
Section: Discussionsupporting
confidence: 92%
“…For pak choi microgreens, no significant differences were observed neither due to the type of light nor to the mixture of growing media. Neugart et al [ 24 ] used a treatment with 5% coffee residue + control (35 % volcanic clay, 50 % turf and 15 % bark humus) and their glucosinolate values in Brassica rap a were lower compared to the treatment without additional coffee. Glucosinolates have been found to be nitrogen-containing compounds, and therefore extra nitrogen input strongly affects their concentration [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Neugart et al [ 24 ] used a treatment with 5% coffee residue + control (35 % volcanic clay, 50 % turf and 15 % bark humus) and their glucosinolate values in Brassica rap a were lower compared to the treatment without additional coffee. Glucosinolates have been found to be nitrogen-containing compounds, and therefore extra nitrogen input strongly affects their concentration [ 24 ]. Regarding the effect of light, Demir et al [ 25 ] observed lower glucosinolate content in cabbage grown with a light treatment including a far red (FR) portion similar to our LED 2.…”
Section: Resultsmentioning
confidence: 99%
“…To enhance the organic benefits, the compost was enriched with the plant-beneficial bacteria and micronutrients. Making the compost biologically active multiplies its agricultural and environmental benefits as the organic and biofertilizers work in synergy ( Neugart et al, 2018 ). The plant-beneficial bacteria are highly active in converting the unavailable forms of nutrients (N, P, Zn, etc .)…”
Section: Discussionmentioning
confidence: 99%